Satisfaction of students toward using test retest method in reading and writing skills for Thai word - Nattharacha Chomphara; Siriphon Srichantha; Atikhun Sintanapanya; Supachai Srichantha (Gemilang Maju Publikasi Ilmiah (GMPI), 2021)
This research study was aimed at the satisfaction of students toward using the test retest method in course Reading and Writing Skills for Thai Word. The research samples consisted of 44 students who were students at Loei Rajabhat University. The research instrument was a questionnaire. Data were analyzed with percentage, mean, and standard deviation. The result showed that the satisfaction level of students toward using the test-retest method in Reading and Writing Skills for Thai Word in overall aspects were at high level. They are ready to improve their learning achievement and language skills. The program or workshop for continuing in such knowledge and language skills need to be prepared in the appropriate contexts.